Biodegradation of Aflatoxin B1 in the Baijiu Brewing Process by Bacillus cereus - Guoli Xue; Yanjun Qu; Dan Wu; Shuyuan Huang; Yuqing Che; Jing Yu; Ping Song (Toxins, 2023)
Aflatoxin is a potent mycotoxin and a common source of grain contamination that leads to great economic losses and health problems. Although distilled baijiu cannot be contaminated by aflatoxin, its presence in the brewing process affects the physiological activities of micro-organisms and reduces product quality. Bacillus cereus XSWW9 capable of degrading aflatoxin B1 (AFB1) was isolated from daqu using coumarin as the sole carbon source. XSWW9 degraded 86.7% of 1 mg/L AFB1 after incubation at 37 °C for 72 h and tolerated up to 1 mg/L AFB1 with no inhibitory effects. Enzymes in the cell-free supernatant of XSSW9 played a significant role in AFB1 degradation. The AFB1-degradation activity was sensitive to protease K and SDS treatment, which indicated that extracellular proteins were responsible for the degradation of AFB1. In order to investigate the AFB1-degradation ability of XSSW9 during the baijiu brewing process, AFB1 and XSWW9 were added to grain fermentation (FG-T) and normal grain fermentation without AFB1, while normal grain fermentation without AFB1 and XSWW9 was used as a control (FG-C). At the end of the fermentation, 99% AFB1 was degraded in the residue of fermented grains. The differences of microbial communities in the fermented grains showed that there were no significant differences between FG-T and FG-C in the relative abundance of dominant genera. The analysis of volatile compounds of their distillation showed that the contents of skeleton flavor components was similar between FG-T and FG-C. These results offer a basis for the development of effective strategies to reduce the effect of AFB1 on the brewing process and ensure that the production of baijiu is stable.